ATTITUDE OF STUDENTS ON CONCEPT MAPPING - AN INNOVATIVE TEACHING LEARNING STRATEGY - T., Nirmala; S., Shakuntala B. (Journal of Health and Allied Sciences NU, 2012)
Background: Multiple researches are going on in the field of promotion of critical thinking skills among nurses and one of the well studied teaching strategies is Concept Mapping (CM). Though Concept mapping is proved to be effective in promotion of critical thinking, it is not widely used. So this study aimed to identify the attitude of student nurses in relation to Concept mapping.Methods: Descriptive survey design was used in this study. Thirty nine pre-final year nursing students participated in this study. 5 point Likert scale was used to assess the attitude of the students. Verbal opinion was also collected in relation to Concept mapping.Results: There were 10 positive and 8 negative statements regarding Concept mapping which the student nurses evaluated. The mean attitude score was 74.5% which showed that the students were in favour of concept mapping. 97% of the students had said that they can easily apply it to the nursing process and 77% of them agreed that it can be used for the entire subjects including non nursing subjects like basic sciences. However, 61% of the students had said the preparation of concept mapping as a time consuming task and they would prefer traditional method of writing care plans. They had expressed that concept mapping made their mind fresh, kindled their thinking and improved their critical thinking. Many of them suggested that if concept mapping was being introduced to them from the first, it would have been the best method to write care plans.Conclusion: As there is acceptance from the student to use concept mapping, it is required to prepare the nurse educators to use concept mapping as one of the teaching method.